1992
DOI: 10.1021/bi00127a026
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the lipoprotein cholesteryl ester transfer process using isolated rat ovary plasma membranes

Abstract: Steroidogenic cells are able to utilize lipoprotein-derived cholesteryl esters for steroidogenesis without internalizing intact lipoproteins. In the current report, we provide evidence that an early step in this process may be the selective extraction of cholesteryl esters at the cell (plasma membrane) surface. We have used a highly purified plasma membrane preparation from rat luteinized ovaries for incubation with rat- and human-derived high density (HDL) and low density (LDL) lipoproteins. The lipoproteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…incubation of cells at 4°C or incubation of cells with NEM permits some plasma membrane uptake of the BODIPY molecule, but completely blocks further internalization of the CEs. The relative temperature-tolerance of the plasma membrane is consistent with earlier work from this laboratory which showed that lipoprotein-CE transport into isolated fractions of rat ovary plasma membrane continues to take place in the cold, albeit at a reduced level (68). Whether this difference in membrane permeability to the BODIPY-CE is due to differences in the composition or physical properties of plasma membranes versus endomembranes (such as differences in the content of free (unesterified) cholesterol which could affect the fluidity of the membranes at low temperatures), or is due to low temperature interference with some essential lipid translocase (69) or NSF (with a role in translocating lipids from one membrane compartment to another) (31), is not yet clear.…”
Section: Discussionsupporting
confidence: 88%
“…incubation of cells at 4°C or incubation of cells with NEM permits some plasma membrane uptake of the BODIPY molecule, but completely blocks further internalization of the CEs. The relative temperature-tolerance of the plasma membrane is consistent with earlier work from this laboratory which showed that lipoprotein-CE transport into isolated fractions of rat ovary plasma membrane continues to take place in the cold, albeit at a reduced level (68). Whether this difference in membrane permeability to the BODIPY-CE is due to differences in the composition or physical properties of plasma membranes versus endomembranes (such as differences in the content of free (unesterified) cholesterol which could affect the fluidity of the membranes at low temperatures), or is due to low temperature interference with some essential lipid translocase (69) or NSF (with a role in translocating lipids from one membrane compartment to another) (31), is not yet clear.…”
Section: Discussionsupporting
confidence: 88%
“…During in situ perfusions of adrenal and luteinized ovarian tissue, the perfused lipoproteins are trapped in such channels and selective uptake of lipoprotein CEs is believed to begin at these sites (1-3, 6, 26). Enriched membrane preparations isolated from the luteinized ovary retain many such microvillar channels in vitro, which are morphologically intact, functionally able to trap lipoproteins, and able to carry out selective HDL-CE uptake (4,27). Recent studies have shown that in all these situations, the doublemembraned channels strongly express the HDL receptor protein, SR-BI.…”
Section: Discussionmentioning
confidence: 99%
“…Light and heavy plasma membrane fractions were isolated by a slight modification of the procedure described previously (16,(30)(31)(32). In brief, pooled ovaries from a group of four superovulated luteinized rats [day 7 post-hCG] or desensitized rats [luteinized ovaries treated with a second (24 h) dose of hCG (25 IU) on day 6] were freed of adhering fat and connective tissue, minced with scissors, and homogenized with 10 strokes in 10 ml of ice-cold STE medium (0.3 M sucrose, 1 M EDTA, and 10 mM Tris-HCl, pH 7.4) at 4 Њ C. After filtration through cheesecloth, the homogenates were subjected to differential centrifugation, and 800 g (10 min) and 20,000 g (20 min) pellets were prepared and used for the isolation of light and heavy plasma membranes, respectively.…”
Section: Isolation Of Light and Heavy Plasma Membrane Fractions From mentioning
confidence: 99%